2013
DOI: 10.1002/cbin.10221
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of bovine colostral odorant‐binding protein (bcOBP) mRNAs in several tissues of bovine body

Abstract: Bovine colostral odorant-binding protein (bcOBP) is a novel protein found in bovine colostrum and belonging to the lipocalin superfamily. Most of them are secretory proteins. We have examined the localisation of bcOBP messenger RNA in several tissues. The expression of bcOBP messenger RNAs was followed in bovine principal organs and female reproductive tracts with in situ hybridisation, but the localisation of it was not detected. The expression levels of bcOBP mRNAs were also extremely low in those tissues. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…OBP derived from nasal mucosa showed low sequences similarity (52%) to bcOBP. Our previous study indicated that bcOBP mRNA was expressed in bovine several tissues without its localization (Katayama and Japaridze, 2014). However, the expression level of bcOBP mRNA and the origin of bcOBP remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…OBP derived from nasal mucosa showed low sequences similarity (52%) to bcOBP. Our previous study indicated that bcOBP mRNA was expressed in bovine several tissues without its localization (Katayama and Japaridze, 2014). However, the expression level of bcOBP mRNA and the origin of bcOBP remain unknown.…”
Section: Introductionmentioning
confidence: 99%